(untitled) (Bangladesh Journal of Medical Science, 2026)
Background Occupational cement dust exposure poses significant health risks, with recent evidence suggesting potential impacts on liver function, particularly in developing countries with expanding cement industries. Objectives This study aimed to evaluate the effect of chronic occupational cement dust exposure on liver function among male adults working in a cement factory in Bangladesh, assessing serum liver enzyme levels as biomarkers of hepatic stress. Methods A cross-sectional study was conducted from September 2017 to August 2018 at Dhaka Medical College, Dhaka, and Ninety-two healthy males aged 20- 50 years were enrolled, including 46 workers exposed to cement dust for at least 2 years working in a Munshiganj-based cement mill in Bangladesh and 46 matched controls with no occupational exposure. Liver enzymes, Serum Glutamic Pyruvic Transaminase (SGPT) and Serum Glutamic-Oxaloacetic Transaminase (SGOT), and alkaline phosphatase (ALP) were assessed using automated analyzers. Statistical analyses included the Mann-Whitney U test, the Pearson correlation coefficient test, and logistic regression. Result Mean liver enzyme levels (SGPT and SGOT) were significantly reduced while serum ALP increased dramatically in exposed workers compared to controls, with a p-value of <0.001. Though all values remained within the normal clinical range, the significant alterations in liver enzymes upon cement dust exposure may indicate early subclinical hepatic stress. The liver enzyme alterations likely reflect chronic, low-level inflammatory and oxidative challenges, with differences attributed to workplace exposure intensity and duration. Conclusions Chronic occupational exposure to cement dust may lead to measurable subclinical alterations in liver enzymes, suggesting early hepatic adaptation or stress despite an absence of overt disease. Regular monitoring and improved workplace safety measures are recommended to mitigate longterm risks. BJMS, Vol. 25 No. 01 January’26 Page : 91-102